Review of Vision-Based Robot Navigation Method - Budi Rahmani; Agfianto Eko Putra; Agus Harjoko; Tri Kuntoro Priyambodo (Institute of Advanced Engineering and Science, 2015)
Vision-based robot navigation is a research theme that continues to be developed up to now by the researchers in the field of robotics. There are innumerable methods or algorithms are developed, and this paper described the reviews of the methods. The methods are distinguished whether the robot is equipped with the navigation map (map-based), the map is built incrementally as robot observes the environment (map-building), or the robot navigates using no map (mapless). In this paper will described navigation methods of map-based, map-building, and mapless category.